Quality of native ejaculate in dog out and during sexual season (VETERINARIA, 2020)
The seasonal influence, i.e. the influence of climatic changes on the dog semen was investigated. Dog age varied between 2-4. German-shepard-type dog body weight was about 25 kg, and the other mixed breed dogs about 9 kg. All were kept in good zoo-hygienic conditions (sunny, ventilated and dry rooms). Dogs were served ready-made pellet food with the daily meals adjusted to their body mass. Experimental researches were mainly performed before and during the sexual season. Sperm from the dogs was taken manually every 5-6 days. After obtaining the ejaculate, the spermsampler was inserted in pre-heated cotton, and brought to the andrologic laboratory. Tools and instruments used for ejaculate sampling were heated to +35°C before use. Quality control was performed with the devices and instruments heated to +38°C in order to avoid detrimental effect of rapid cooling to sperm movement, metabolism, etc. Sampled native ejaculates were anylized for the volume, motility, concentration, etc.
Keywords: dog; sperm; sexual season